Examining the Association Between Tax Knowledge and Compliance Among Sole Proprietors in Olongapo City: A Moderation Study - John Kyro Mendoza; Raven Choy Pungloy; Frances Jhanine Reyes; Nessa Belle Rull; Crizzalin Eve Supnet; Samantha Claire Vitug; Ediric Gadia (Future Science / FSH-PH Publications, 2026)
This study aimed to explore the relationship between tax knowledge and level of compliance of individual taxpayers in Olongapo City, focusing specifically on the influence of variables such as age, education, income, and whether the taxpayer employs an accountant or tax professional. This study used a quantitative correlational design with data-collection done through a survey among 54 registered sole proprietors. The researcher used a combination of descriptive statistics, correlation analysis, and moderation analysis for the data gathered. The results indicated that the overall tax knowledge among the respondents was very high, as well as the overall compliance rates. Correlation analysis revealed a strong and statistically significant positive relationship between tax knowledge and tax compliance (r values ranging from 0.744 to 0.891, p < .001), indicating that higher levels of tax knowledge are associated with better compliance in terms of timeliness and accuracy. Furthermore, moderation analysis showed that while tax knowledge positively predicts compliance, this link varies by demographics and operations: stronger for males (ẞ = .346, p = .008), lower- income proprietors (ẞ = -.107, p = .019), and those not hiring accountants (ẞ = -.477, p < .001, indicating a substitution effect where personal knowledge drives compliance without professionals), but unaffected by education, ẞ = -.082, p = .213).